Le caveau de l’église Saint-Pierre d’Épernon (Eure-et-Loir) et ses vestiges : protocole d’étude et premiers résultats - Philippe Blanchard; Sacha Kacki; Jérôme Rouquet; Matthieu Gaultier (Revue Archéologique du Centre de la France)
An archaeological excavation undertaken in the burial vault of the Saint-Pierre church in Épernon led to the discovery of various archaeological remains (ossuary, mummified bodies, sawn skulls, and tombstone), most of which date back to the Modern period. The study reveals specific burial practices. The paper examines the history of this burial place, the aims of its study, and the main results, with particular focus on the protocol developed to study the ossuary. Results underline the usefulness of the analysis of such kind of funerary feature. They highlight links between partially preserved mummified remains and some bones scattered in an ossuary that have been rearranged many times.